Upaya Meningkatkan Hasil Belajar Siswa dengan Menggunakan Strategi Omaggio pada Mata Pelajaran Bahasa Indonesia Tingkat Madrasah Ibtidaiyah - Darmawan, Iwan; Nurteti, Lilis; Meidawaty, Sri (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2019)
This research is motivated by the low learning outcomes of students of grade V Madrasah Ibtidaiyah Thoriqun Najah on learning Indonesian language subject matter elements. In an effort to improve student learning outcomes, researchers used the